Composite material based on fungus derived carbon as well as preparation method and application of composite material

By embedding Pt atoms in fungal derived carbon materials, Pt@Fe/BCMs-X composite material was prepared, which solved the problem of slow kinetics of the cathode oxygen reduction reaction of fuel cells, and achieved efficient and stable catalytic performance and cost-reducing effect.

CN119601690AActive Publication Date: 2025-03-11NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411646321.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The kinetics of cathode oxygen reduction reaction of existing fuel cells are relatively slow, resulting in high cost of catalysts and unstable performance.

Method used

Using a composite material based on fungal derived carbon, through the "domain anchoring" strategy, metal Pt atoms were embedded into a substrate with abundant defects, and Pt@Fe/BCMs-X composite material was prepared as a catalyst for oxygen reduction reaction.

Benefits of technology

The catalytic activity and stability of the oxygen reduction reaction are significantly improved, the production cost of the catalyst is reduced, and good performance is maintained under high cycle times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601690A_ABST
    Figure CN119601690A_ABST
Patent Text Reader

Abstract

The invention provides a composite material based on fungus-derived carbon and a preparation method and application thereof, and relates to the technical field of composite materials, and the composite material is prepared by taking fungus-derived carbon as a substrate and loading metal platinum and metal iron. The method has important practical significance in the aspect of developing oxygen reduction electrocatalysts with high activity and high stability, and a new solution is provided for performance improvement of fuel cells and metal-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a composite material based on fungus-derived carbon and a preparation method and application thereof. Background Art

[0002] Modern society's dependence on traditional fossil fuels such as coal, oil and natural gas has not only exacerbated the energy crisis, but also led to global warming and environmental pollution, greatly threatening the quality of life and health of human beings. In this context, it has become an urgent need to develop resource-saving, environmentally friendly renewable and sustainable fuels to replace fossil energy. Fuel cells, as a highly efficient device that converts chemical energy into electrical energy through electrochemical pathways, have attracted widespread attention in recent years due to their excellent energy density and environmental protection characteristics. Taking proton exchange membrane fuel cells (PEMFCs) as an example, their operation process involves the oxidation reaction (HOR) of anode fuels such as hydrogen, where hydrogen is converted into protons and electrons at the anode. Subsequently, protons are transferred to the cathode with the help of a proton exchange membrane, or electrons are transferred to the cathode through an external circuit. At the cathode, oxygen generates water through an electron reduction reaction (ORR) coupled with protons. However, since the cathode ORR is limited by the adsorption and desorption rates of reactants, intermediates and products on the electrode surface, its kinetic process is relatively slow. Therefore, the cathode reaction of commercial fuel cells usually relies on electrocatalysts. In the development of modern electrocatalysts, selecting suitable metal components and substrate materials is an important strategy to improve catalytic performance and economic feasibility. The combination of platinum (Pt) and iron (Fe) shows significant advantages in catalyst design. Pt is well-known for its excellent ORR catalytic activity and is a key material for improving the efficiency of fuel cells. However, due to the high cost of Pt, finding ways to reduce its usage has become a research focus. As a cheap and abundant metal, Fe can not only reduce the overall cost of the catalyst by combining with platinum, but also enhance the catalytic performance and stability of platinum through electronic and structural effects. In addition, Pt-Fe alloys may produce a synergistic effect, further improving the durability and versatility of the catalyst.

[0003] At the same time, fungus-derived carbon also shows great potential as a substrate material. It is widely available and renewable, with low preparation cost, which meets the requirements of sustainable development. The natural porous structure of fungal biomass can provide a high specific surface area after carbonization, which helps to improve the activity and stability of the catalyst. In addition, after proper treatment, fungus-derived carbon exhibits good conductivity and chemical stability, and can maintain performance in harsh electrochemical environments. Its surface chemical properties can be optimized by regulating the preparation conditions to enhance the binding force with metal nanoparticles.

[0004] Therefore, developing low-cost and efficient electrocatalysts to replace commercial platinum catalysts, especially studying the relationship between the composition and structure of electrocatalysts and fuel cell performance (activity and stability), is not only of great scientific value, but also of far-reaching economic significance. These studies will provide strong support for achieving sustainable energy conversion and reducing environmental burden. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention proposes a composite material based on fungus-derived carbon and a preparation method and application thereof.

[0006] In a first aspect, the present invention provides a composite material based on fungus-derived carbon, wherein the composite material is made by using fungus-derived carbon as a substrate and loading metal platinum and metal iron.

[0007] In a second aspect, the present invention provides a method for preparing the composite material, comprising the following steps: S1, washing the fungal material, freeze-drying to obtain freeze-dried fungi, and crushing the freeze-dried fungi to obtain fungal powder; S2, calcining the fungus powder under an argon atmosphere to obtain a fungus-derived carbon material BCMs-X, wherein X represents a fungus material; S3, the BCMs-X and ZnCl 2 and FeCl 3 6H 2 After O grinding, Fe / BCMs-X was obtained by annealing and washing in an argon-hydrogen mixed gas atmosphere (hydrogen content was 10%); S4, the Fe / BCMs-X and NaBH 4 and K 2 PtCl 6 Dispersed in ethylene glycol, heated to 50-70°C, kept warm for 10-14 hours, and washed to obtain the Pt@Fe / BCMs-X composite material.

[0008] Preferably, the fungal material is selected from Pleurotus ostreatus, Pleurotus eryngii or Flammulina velutipes.

[0009] Preferably, in S2, the heating rate of calcination is 5°C / min, the calcination temperature is 290-310°C, and the calcination time is 1h.

[0010] Preferably, in S3, the BCMs-X, ZnCl 2 and FeCl 3 6H 2 The mass ratio of O is 1:1:6.

[0011] Preferably, in S3, the BCMs-X, ZnCl 2 and FeCl3 6H 2 The three are ground into a thin paste and then annealed. The annealing heating rate is 5°C / min, the annealing temperature is 800-900°C, and the time is 2h.

[0012] Preferably, in S3, the specific operation of washing is: washing the annealed product with 10% nitric acid to remove unstable metal substances and residues, and vacuum drying at 30-50° C. for 6-18 hours.

[0013] Preferably, in S4, the Fe / BCMs-X, NaBH 4 and K 2 PtCl 6 The mass ratio of the above-mentioned compounds is 4:10:15, the volume of the above-mentioned ethylene glycol is 30 mL, and the above-mentioned temperature increase is performed by heating the above-mentioned compounds in an oil bath to 50-70° C.

[0014] Preferably, in S4, the specific operation of washing is: washing the product after insulation with water to remove residues, centrifuging at 14000 rpm for 5 minutes, and vacuum drying the separated solid product at 30-50°C for 6-18 hours.

[0015] In a third aspect, the present invention further provides the use of the composite material or the Pt@Fe / BCMs-X composite material obtained by the preparation method as a cathode catalyst for oxygen reduction reaction in a 0.1 mol / L KOH electrolyte.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention proposes a composite material based on fungus-derived carbon, and its preparation method and application. The material Pt@Fe / BCMs-X is an innovative multi-metal composite material. Through the "confined anchoring" strategy, the metal Pt atoms are precisely embedded into the defect-rich substrate. This strategy effectively adjusts the interfacial interactions, coordination and electronic environment of the catalyst, which not only increases the number of catalytic active centers, but also promotes the efficient transfer of electrons, thereby significantly improving the catalytic activity and stability of ORR. The present invention uses fungus materials as carbon-based materials, and the preparation process is simple and low-cost. Therefore, the invention has important practical significance for replacing traditional Pt / C catalysts in applications as fuel cell cathode catalysts. This innovation not only provides a feasible solution for reducing production costs, but also plays an important role in improving fuel cell performance and sustainable development.

[0017] 2. The Pt@Fe / BCMs-X composite material prepared by the present invention is used as an oxygen reduction reaction catalyst in 0.1 mol / L KOH electrolyte, and has a half-wave potential of 0.86-0.89 V, which is greater than the half-wave potential of 0.85 V of commercial Pt / C. After 10,000 CV cycles, the half-wave potential drops by 10-15 mV, which is less than the half-wave potential drop of 19 mV of commercial Pt / C after 10,000 CV cycles. The composite material has better activity and stability than commercial Pt / C. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a transmission electron microscope image of the Fe / BCMs-X material in an embodiment of the present invention.

[0019] Figure 2 This is a transmission electron microscope image of the Pt@Fe / BCMs-X material in an embodiment of the present invention.

[0020] Figure 3 This is a comparison chart of XRD between Fe / BCMs-X and Pt@Fe / BCMs-X materials in the embodiment of the present invention.

[0021] Figure 4 This is the Raman spectrum diagram of Fe / BCMs-X and Pt@Fe / BCMs-X materials in the embodiments of the present invention.

[0022] Figure 5 XPS graphs of Fe / BCMs-X and Pt@Fe / BCMs-X materials in the embodiments of the present invention; wherein, (a) is the N 1s spectrum of Fe / BCMs-X, (b) is the N 1s spectrum of Pt@Fe / BCMs-X, (c) is the Fe 2p spectrum of Pt@Fe / BCMs-X, and (d) is the Pt 4f spectrum of Pt@Fe / BCMs-X.

[0023] Figure 6 1 is a comparison diagram of the oxygen reduction performance of Fe / BCMs-X and Pt@Fe / BCMs-X materials in the embodiment of the present invention; wherein (a) is a linear voltammetric scan diagram of oxygen reduction, and (b) is a comparison diagram of half-wave potential and kinetic current density at 0.85V.

[0024] Figure 7 The linear voltammetric scan diagrams of Pt@Fe / BCMs-X at different scan rates and the KL equation diagrams at different potentials in the embodiments of the present invention; wherein (a) is Pt@Fe / BCMs-A, (b) is Pt@Fe / BCMs-B, and (c) is Pt@Fe / BCMs-C; Figure 8These are the linear voltammetric scans of the Pt@Fe / BCMs-X material in the embodiment of the present invention and commercial 20wt% Pt / C initially and after 10,000 CV cycles; where (a) is Pt@Fe / BCMs-A, (b) is Pt@Fe / BCMs-B, (c) is Pt@Fe / BCMs-C, and (d) is 20wt% Pt / C. DETAILED DESCRIPTION

[0025] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0026] Example 1: A method for preparing a composite material based on fungus-derived carbon, comprising the following steps: S1. Carbonization of fungi: Wash the oyster mushrooms, put them into a freeze dryer for freeze drying, and obtain freeze-dried oyster mushrooms. The freeze-dried oyster mushrooms are crushed to obtain oyster mushroom powder.

[0027] S2. The Pleurotus ostreatus powder is heated to 300° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept warm for 1 hour to obtain a fungus-derived carbon material BCMs-A, wherein A represents Pleurotus ostreatus.

[0028] S3. At room temperature, weigh 0.1 g BCMs-A, 0.1 g ZnCl 2 and 0.6 g FeCl 3 6H 2 O was ground into a thin paste in a mortar and then transferred to a porcelain boat. It was heated to 850°C at a heating rate of 5°C / min in an argon-hydrogen mixed gas (hydrogen content was 10%) atmosphere and kept warm for 2 hours. After cooling to room temperature, it was soaked in 10% nitric acid for 6 minutes, washed with water until neutral, and dried in a 40°C vacuum drying oven for 12 hours to obtain Fe / BCMs-A.

[0029] S4. At room temperature, weigh 40 mg Fe / BCMs-A into a three-necked flask, then weigh 30 mL ethylene glycol and add it into the three-necked flask. After mixing evenly on a magnetic stirrer, weigh 100 mg NaBH 4 and 150 mg K 2 PtCl 6 Add to the three-necked flask, stir evenly again, put into a 60°C oil bath, keep warm for 12 hours while stirring, cool to room temperature, put into a centrifuge, and centrifuge at 14000 rpm for 5 minutes. Wash the obtained precipitate three times with water, and dry it in a vacuum drying oven at 40°C for 13 hours to obtain a Pt@Fe / BCMs-A composite material.

[0030] Example 2: A method for preparing a composite material based on fungus-derived carbon, comprising the following steps: S1. Carbonization of fungi: Wash the Pleurotus eryngii, put it into a freeze dryer for freeze drying, obtain freeze-dried Pleurotus eryngii, and grind the freeze-dried Pleurotus eryngii to obtain Pleurotus eryngii powder.

[0031] S2. The Pleurotus eryngii powder is heated to 290° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept warm for 1 hour to obtain a fungus-derived carbon material BCMs-B, wherein B represents Pleurotus eryngii.

[0032] S3. At room temperature, weigh 0.1 g BCMs-B, 1 g ZnCl 2 and 1g FeCl 3 6H 2 O was ground into a thin paste in a mortar and then transferred to a porcelain boat. It was heated to 900°C at a heating rate of 5°C / min in an argon-hydrogen mixed gas (hydrogen content was 10%) atmosphere and kept warm for 2 hours. After cooling to room temperature, it was soaked in 10% nitric acid for 5 minutes, washed with water until neutral, and dried in a 50°C vacuum drying oven for 6 hours to obtain Fe / BCMs-B.

[0033] S4. At room temperature, weigh 50 mg Fe / BCMs-B into a three-necked flask, then weigh 30 mL ethylene glycol and add it into the three-necked flask. After mixing evenly on a magnetic stirrer, weigh 100 mg NaBH 4 and 200 mg K 2 PtCl 6 Add to the three-necked flask, stir evenly again, put into a 50°C oil bath, keep warm for 14 hours while stirring, cool to room temperature, put into a centrifuge, and centrifuge at 14000 rpm for 5 minutes. Wash the obtained precipitate three times with water, and dry it in a vacuum drying oven at 30°C for 18 hours to obtain a Pt@Fe / BCMs-B composite material.

[0034] Example 3: A method for preparing a composite material based on fungus-derived carbon, comprising the following steps: S1. Carbonization of fungi: Wash the Flammulina velutipes, put them into a freeze dryer for freeze drying, and obtain freeze-dried Flammulina velutipes. Grind the freeze-dried Flammulina velutipes to obtain Flammulina velutipes powder.

[0035] S2. The Flammulina velutipes powder is heated to 310° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept warm for 1 hour to obtain a fungus-derived carbon material BCMs-C, wherein C represents Flammulina velutipes.

[0036] S3. At room temperature, weigh 1g BCMs-C, 0.1g ZnCl 2 and 2 g FeCl 3 6H 2O was ground into a thin paste in a mortar and then transferred to a porcelain boat. It was heated to 800°C at a heating rate of 5°C / min in an argon-hydrogen mixed gas (hydrogen content was 10%) atmosphere and kept warm for 2 hours. After cooling to room temperature, it was soaked in 10% nitric acid for 8 minutes, washed with water until neutral, and dried in a 30°C vacuum drying oven for 18 hours to obtain Fe / BCMs-C.

[0037] S4. At room temperature, weigh 40 mg Fe / BCMs-C into a three-necked flask, then weigh 30 mL ethylene glycol and add it into the three-necked flask. After mixing evenly on a magnetic stirrer, weigh 150 mg NaBH 4 and 100 mg K 2 PtCl 6 Add to the three-necked flask, stir evenly again, put into a 70°C oil bath, keep warm for 10 hours while stirring, cool to room temperature, put into a centrifuge, and centrifuge at 14000 rpm for 5 minutes. Wash the precipitate three times with water, and dry it in a vacuum drying oven at 50°C for 6 hours to obtain a Pt@Fe / BCMs-C composite material.

[0038] The materials obtained in Examples 1-3 were respectively subjected to transmission electron microscopy, and the obtained transmission electron microscopy images are as follows: Figure 1 , 2 As shown, Figure 1 (a) represents Fe / BCMs-A, Figure 1 (b) represents Fe / BCMs-B, Figure 1 (c) represents Fe / BCMs-C. Figure 2 (a) represents Pt@Fe / BCMs-A, Figure 2 (b) represents Pt@Fe / BCMs-B, Figure 2 (c) represents Pt@Fe / BCMs-C.

[0039] according to Figure 1-Figure 2 It can be seen that Fe / BCMs-X (X=A / B / C) presents an amorphous sheet structure. After doping with Pt, the formed Pt@Fe / BCMs-X shows that ultra-small nanoparticles with a diameter of less than 5 nanometers grow on the nanosheets in the electron microscope morphology characterization. Combined with the XRD spectrum ( Figure 3 a), it can be observed that Fe / BCMs-X does not have any diffraction peaks, indicating that it is an amorphous structure, which is consistent with the result that no lattice fringes were observed in the electron microscope image. In the XRD spectrum of Pt@Fe / BCMs-X ( Figure 3 b), the Pt crystal phase is clearly shown, and the electron microscope image shows that the nanoparticles on the nanosheets are mainly composed of Pt. Figure 4 Compared with Fe / BCMs-X, the Raman spectra of Pt@Fe / BCMs-X materials D :IG The decrease in the value indicates that the number of defects is reduced, which further proves that the Pt atoms are confined in the defects.

[0040] The high-resolution N 1s XPS spectrum shows that the pyridinic N and pyrrolic N in the carbon layer have a strong affinity for Fe-N. x The formation of bonds has a significant contribution (e.g. Figure 5 This proves that in Fe / BCMs-X and Pt@Fe / BCMs-X, nitrogen atoms are chemically bonded to metallic iron and single Fe atoms may be formed in the materials. Figure 5 c shows the 2p XPS spectrum of iron in Pt@Fe / BCMs-X, indicating that iron exists in a mixed valence state of +2 and +3 in this material. Figure 5 d shows the 4f XPS spectrum of Pt in Pt@Fe / BCMs-X, which shows that Pt exists in a mixed valence state of 0 and +2 in this material, indicating that Pt exists in different coordination environments, among which Pt 0 Combined with the defect sites of carbon materials, Pt 2+ This may be due to partial binding of some Pt ​​with oxygen or surface oxidation when exposed to air.

[0041] Example 4: Pt@Fe / BCMs-A, Pt@Fe / BCMs-B, and Pt@Fe / BCMs-C obtained in Examples 1-3 were subjected to the following operations: 5 mg of the composite material was placed in a centrifuge tube, 600 μL of ethanol, 380 μL of deionized water, and 20 μL of 5% naphthol were placed in the centrifuge tube using a pipette, and ultrasonicated for 1.5 h to obtain a uniformly dispersed ink. The ink was dropped onto an activated glassy carbon rotating disk electrode (loading 0.2857 mg / cm 2 ), and then add 4 μL of 0.1% naphthol to seal the electrode surface to prevent the catalyst from falling off.

[0042] The electrochemical property test was carried out on an Autolab electrochemical workstation using a three-electrode system. The rotating disk electrode to which the catalyst was added was the working electrode, the platinum sheet was the counter electrode, mercuric oxide was the reference electrode, and the electrolyte was a potassium hydroxide solution with a concentration of 0.1 mol / L. All electrochemical tests were carried out at room temperature.

[0043] The electrochemical property test includes cyclic voltammetry and linear sweep voltammetry test. Before the cyclic voltammetry test, high-purity nitrogen was introduced into the electrolyte to saturation to remove the air in the electrolyte. The scanning range of the cyclic voltammetry was 0V to 1V, and the scanning rate was 100mV / s. The unstable substances on the electrode surface were removed by 40 cycles of cyclic voltammetry to form a stable interface, and then the linear sweep voltammetry test was performed. Before the linear sweep voltammetry test, high-purity oxygen was introduced into the electrolyte to saturation to remove the air in the electrolyte. The scanning range of the linear sweep voltammetry test was 0 V to 1 V, the scanning rate was 5mV / s, the rotation speed was 1600rmp, and the half-wave potential was used as the main parameter for comparing the catalyst activity. Linear sweep voltammetry tests were performed at different rotation speeds, and the electron transfer number and kinetic current density were calculated by the KL equation.

[0044] Thanks to the excellent interfacial charge and mass transfer properties, the prepared Pt@Fe / BCMs-A composite material exhibits excellent performance in ORR. The half-wave potential of Pt@Fe / BCMs-A reaches 0.89V, and the kinetic current density is 12.94mA / cm at 0.85V. 2 , which is better than the half-wave potential of the benchmark Pt / C of 0.85V and the kinetic current density of 5.34mA / cm 2 (See Figure 6 ). Calculated by the Koutecky-Levich (KL) equation, the electron transfer number of Pt@Fe / BCMs-A is about 4 (see Figure 7 a). In addition, due to the confined anchoring effect on the Fe / BCMs-A surface, the half-potential of Pt@Fe / BCMs-A only decreased by 15 mV after 10,000 cycles of cyclic voltammetry (CV) testing (see Figure 8 a), while Pt / C dropped by 19 mV under the same conditions (see Figure 8 d), showing that Pt@Fe / BCMs-A is slightly better than Pt / C in terms of stability.

[0045] Similarly, the prepared Pt@Fe / BCMs-B has excellent ORR performance, among which the performance of Pt@Fe / BCMs-B material is close to that of Pt@Fe / BCMs-A, with a half-wave potential of 0.87 V and a kinetic current density of 10.73 mA / cm at 0.85 V. 2 (See Figure 6 ). Calculated by KL equation, the electron transfer number of Pt@Fe / BCMs-B is about 4 (see Figure 7 b) After 10,000 CV cycles of stability testing, the half-wave potential of Pt@Fe / BCMs-B dropped by 10 mV ( Figure 8 b).

[0046] Similarly, the prepared Pt@Fe / BCMs-C has excellent ORR performance, among which the performance of Pt@Fe / BCMs-C material is close to that of Pt@Fe / BCMs-B, with a half-wave potential of 0.86 V and a kinetic current density of 7.37 mA / cm at 0.85 V. 2 ( Figure 6 ), calculated by KL equation, the electron transfer number of Pt@Fe / BCMs-C is about 4 ( Figure 7 c). After 10,000 CV cycles of stability testing, the half-wave potential of Pt@Fe / BCMs-C dropped by 12 mV ( Figure 8 c) The above are only implementation modes of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent schemes made using the contents of the present invention specification, directly or indirectly applied in other related technical fields, are also within the patent protection scope of the present invention.

Claims

1. A composite material based on fungus-derived carbon, characterized in that: The composite material is made by using fungus-derived carbon as a substrate to load metal platinum and metal iron.

2. The method for preparing the composite material according to claim 1, characterized in that: The steps include: S1, washing the fungal material, freeze-drying to obtain freeze-dried fungi, and crushing the freeze-dried fungi to obtain fungal powder; S2, calcining the fungus powder under an argon atmosphere to obtain a fungus-derived carbon material BCMs-X, wherein X represents a fungus material; S3, grinding the BCMs-X with ZnCl2 and FeCl3·6H2O, annealing in an argon-hydrogen mixed gas atmosphere, and then washing to obtain Fe / BCMs-X; S4. Disperse the Fe / BCMs-X, NaBH4 and K2PtCl6 in ethylene glycol, raise the temperature to 50-70°C, keep the temperature for 10-14 hours, and obtain the Pt@Fe / BCMs-X composite material after washing.

3. The preparation method according to claim 2, characterized in that: The fungus material is selected from Pleurotus ostreatus, Pleurotus eryngii or Flammulina velutipes.

4. The preparation method according to claim 2, characterized in that: In S2, the calcination heating rate is 5°C / min, the calcination temperature is 290-310°C, and the calcination time is 1h.

5. The preparation method according to claim 2, characterized in that: In S3, the mass ratio of BCMs-X, ZnCl2 and FeCl3·6H2O is 1:1:

6.

6. The preparation method according to claim 2, characterized in that: In S3, the BCMs-X, ZnCl2 and FeCl3·6H2O are ground into a thin paste and then annealed. The annealing heating rate is 5°C / min, the annealing temperature is 800-900°C, and the annealing time is 2h.

7. The preparation method according to claim 2, characterized in that: In S3, the specific operation of washing is: washing the annealed product with 10% nitric acid to remove unstable metal substances and residues, and vacuum drying at 30-50° C. for 6-18 hours.

8. The preparation method according to claim 2, characterized in that: In S4, the mass ratio of the Fe / BCMs-X, NaBH4 and K2PtCl6 is 4:10:15, the volume of the ethylene glycol is 30 mL, and the temperature is increased by heating in an oil bath to 50-70°C.

9. The preparation method according to claim 2, characterized in that: In S4, the specific operation of washing is: washing the product after incubation with water to remove residues, centrifuging at 14000 rpm for 5 minutes, and vacuum drying the separated solid product at 30-50°C for 6-18 hours.

10. Use of the composite material according to claim 1 or the Pt@Fe / BCMs-X composite material obtained by the preparation method according to any one of claims 2 to 9 as a cathode catalyst for oxygen reduction reaction in 0.1 mol / L KOH electrolyte.

Citation Information

Patent Citations

  • Modified catalyst for low-temperature fuel cell and preparation method thereof

    CN101572316A

  • Cobweb-based porous activated carbon fiber material and application

    CN105633424A

  • Biomass carbon material derived transition metal-based catalyst, preparation method and application thereof, and solid-state zinc-air battery

    CN113571719A

  • Porphyrin-derived carbon-based PtFe alloy material, preparation method and application thereof, air electrode and fuel cell

    CN114984975A